Balance and perspectives of education for indigenous populations in Peru: 1990 - Pozzi-Escot, Inés (1990)
Education for the indigenous populations of Peru has gone through different struggles, debates and conceptualizations in this century that serve as a background to the present situation and that have not necessarily been canceling instances. The debate continues, although somewhat deafened by the weight of new national tribulations.